A proposed sustainability index for synthesis plans based on input provenance and output fate: application to academic and industrial synthesis plans for vanillin as a case study - Andraos, John (Beilstein Journal of Organic Chemistry, 2020)
This paper describes a sustainability index (SI) as a quantitative measure of “sustainability” applicable to synthesis plans based on the provenance of input materials and energy sources and the fate of output waste products. The index is computed as the root-mean-square average of the following four parameters: mass fraction of valorized inputs (FVI), mass fraction of valorized outputs (FVO), mass fraction of valorized target product (FVP), and input enthalpic energy fraction arising from renewable energy sources (FRE). Valorized input materials originate from renewable, recycled, or reclaimed sources. Valorized output materials are destined for recycling or reclaiming so that they may be used in the same or other chemical processes. Valorized target product refers to that portion of the target product that is actually used for its intended purpose. Renewable energy sources are defined as originating from hydroelectric, wind, solar, geothermal, and biomass sources. The computation of SI is illustrated for 22 synthesis plans of the high commodity flavour ingredient vanillin from biofermentation, chemical synthesis, and solvent extraction processes. In addition, these plans are compared and ranked according to Borda count and poset (partially ordered set) pairwise dominance analyses using the following attributes: process mass intensity (PMI), sacrificial reagent (SR) consumption, input enthalpic energy (IEE) consumption, Rowan solvent greenness index (RSGI), and sustainability index (SI).
Keywords: Borda count; green chemistry; input enthalpic energy; process mass intensity; poset dominance analysis; Rowan solvent greenness index; sacrificial reagent; sustainability; sustainable chemistry